Expectancy on Being Older Persons and Self-Preparation for Old Age in Middle-Adults: Bang Phlad, Bangkok Metropolis - Jirojanakul, Pragai; Leesukol, Nipa; Kwanyuen, Renu; Kaewpan, Wanpen (Journal of Food Health and Bioenvironmental Science, 2023)
The purposes of this study were to assess the level of expectancy on being older persons and of the self-preparation for old age in middle-aged adults (ages between 35-60 years); and to estimate an equation to predict the self-preparation of middle-aged adults from the demographic factors and the expectancy on being older persons. The sample of 400 persons were recruited from middle-aged adults who were qualified with the predetermined criteria, using multi-stage random sampling technique. Data was collected using the questionnaire, developed by the researchers, consisted of 3 sections: the personal data, the expectancy on being older persons and the self-preparation for old age. The CVIs of sections 2 and 3 of the questionnaire were 0.97 and 1.0 with reliabilities of 0.92 and 0.93 respectively. It was found that the expectancy of the sample on being older persons in general was at a high level (Mean 4.07, S.D. 0.66) and the self-preparation for old age in general was also at a high level (Mean 4.00, S.D. 0.55). The variables, which were analyzed using chi-square tests and Pearson’s Product Moment Correlation test and found significantly associated with the self-preparation for old age, were later included to formulate a prediction equation of the dependent variable. The Stepwise multiple regression analysis revealed the equation that best predicted the self-preparation for old age, with the Coefficient of determination (R2) of 0.467 (R=.685). The equation included independent variables as follows: the expectancy on being older persons on spiritual and physical aspects, working for government/state enterprise/private company, practicing Buddhism, and having education at vocational certificate or higher levels. The implications of research findings and recommendations for future practice were discussed.